Toxicidad aguda del extracto alcohólico e hidroalcohólico de hojas y corteza de Artocarpus altilis en nauplios de Artemia franciscana - Valera Pereira, Emily Jazmin (2024)
The Artemia assay is one of the most used bioassays, since it determines the lethal effect of materials on Artemia larvae, and in this way a wide range of pharmacological effects is predicted. Artocarpus altilis, commonly known as tree bread, contains large amounts of phenolic compounds to which diverse bioactivity is attributed. Objective: to determine the acute toxicity of the alcoholic and hydroalcoholic extract of leaves and bark of Artocarpus altilis in nauplii of Artemia franciscana. Methodology: Organs of the species under study collected for convenience, subsequently used in the preparation of alcoholic and hydroalcoholic extract evaluated at 10, 100 and 1000 ppm in nauplii of A. franciscana. Results: The LC50 obtained is > 1000 ppm for both extracts. Conclusion: the alcoholic and hydroalcoholic extracts of leaves and bark of A. altilis do not present acute toxicity at the concentrations evaluated.